Preliminary results of a prospective study on the efficacy and safety of single-session radiofrequency ablation in treating benign thyroid nodules - Nguyen, Van Bang; Le, Van Chi; Le, Trong Binh (Tạp chí Y Dược Huế, 2025)
Objective: This study aimed to assess the safety and effectiveness of radiofrequency ablation (RFA) for benign thyroid nodules and identify independent factors affecting nodule volume reduction rates at one and six months post-treatment. Materials and Methods: Conducted at a single medical center, this prospective study included 80 benign thyroid nodules in 68 patients undergoing RFA. The procedures employed two key techniques: the trans-isthmic and moving-shot approaches. Clinical and ultrasound evaluations were performed at one and six months after treatment. The primary outcomes measured were the volume reduction ratio (VRR) at these intervals, while secondary outcomes included therapeutic success rates and complication rates. Multiple linear regression analysis was applied to pinpoint independent factors influencing VRR. Results: The study followed 68 patients with 80 nodules over one and six months. The average VRR was 41.00% at one month and 69.65% at six months, with an 82.9% therapeutic success rate at the six-month mark. Symptom and cosmetic scores showed significant improvement after one month, while thyroid function remained stable. Three cases of minor complications (temporary voice changes) were noted. Regression analysis indicated that both the internal component and initial volume of nodules were significantly associated with VRR at the one- month follow-up, while no significant associations were found between VRR at 6 months and any clinical or ultrasound features. Conclusion: RFA was shown to be a safe and effective treatment for benign thyroid nodules, offering an alternative therapeutic option with promising outcomes.